Evaluation of the use life of semi-hard cheeses with edible coatings using ginger essential oil (Zingiber officinale) as an antimicrobial agent - Tapiero Cuellar, Jose Libardo; Soleno Wilches, Ronald; Rosero Rivera, Mayra Alejandra; Rivas Rivera, Yessika Marcela; Lozada Perdomo, Andrés Felipe; Blandon Romero, Ángela Vanesa; Ramírez Murillo, Dayan Katherine (Revista Colombiana de Investigaciones Agroindustriales, 2017)
The use of biodegradable materials has made it possible to replace plastic packaging to a large extent. Edible coatings from polysaccharides have become an attractive and cost-effective alternative for food preservation. For this work, carboxymethylcellulose (CMC) films (1.5, 2.0, 2.5%) were used incorporating glycerol as a plasticizer (5%) and essential oil (AE) (0.05, 0.1 mL / L) of ginger (Zingiber officinale) as an antimicrobial agent for the conservation of paipa-like semi-mature cheeses. The extraction of AE from ginger (Zingiber officinale) was carried out, as well as the identification of its main components. For the physicochemical effect tests of the rhizome (Rz) (moisture 84.79, ash 1.39 proteins 2.27, fat 4.12, fiber 0.62, carbohydrates 5.78) were performed on the analyzed species. The essential oil was obtained by microwave-assisted hydrodistillation (MWHD) in a time of 60 minutes (divided into intervals of 15 minutes), with a final separation by Rota evaporation. The yields obtained were 0.15-0.25% with respect to the wet weight. The physical characteristics of the samples showed values of refractive index of 1.52, density 0.88 g / ml and solubility in ethanol at 96º of purity. The analysis of the essential oil was performed by GC-MS, finding a high content of sesquiterpenes, such as zingiberene (7.2-8.5%) and a-curcumene (2.8-3.3%). Semi-mature cheeses were coated, and stored under shelf conditions (15°C, 80% RH), evaluating for 24 days the growth inhibition of the predominant microbiota in this type of food (Penicillium, Aspergillius, Geotrichum, Mucor sp and Fusarium). The RC for CMC 2.5; AE 0.1 mL and glycerol of 5% presented significant differences (<0.5) with respect to the reduction of the microbial load for the final product, becoming an agroindustrial alternative for the conservation of cheeses.